Tuberculosis Treatment Compliance Under Smartphone-Based Video-Observed Therapy Versus Community-Based Directly Observed Therapy: Cluster Randomized Controlled Trial - Ponlagrit Kumwichar; Tagoon Prappre; Virasakdi Chongsuvivatwong (JMIR Publications, 2024)
BackgroundThere are no recent studies comparing the compliance rates of both patients and observers in tuberculosis treatment between the video-observed therapy (VOT) and directly observed therapy (DOT) programs. ObjectiveThis study aims to compare the average number of days that patients with pulmonary tuberculosis and their observers were compliant under VOT and DOT. In addition, this study aims to compare the sputum conversion rate of patients under VOT with that of patients under DOT. MethodsPatient and observer compliance with tuberculosis treatment between the VOT and DOT programs were compared based on the average number of VOT and DOT compliance days and sputum conversion rates in a 60-day cluster randomized controlled trial with patients with pulmonary tuberculosis (VOT: n=63 and DOT: n=65) with positive sputum acid-fast bacilli smears and 38 observers equally randomized into the VOT and DOT groups (19 observers per group and n=1-5 patients per observer). The VOT group submitted videos to observers via smartphones; the DOT group followed standard procedures. An intention-to-treat analysis assessed the compliance of both the patients and the observers. ResultsThe VOT group had higher average compliance than the DOT group (patients: mean difference 15.2 days, 95% CI 4.8-25.6; P=.005 and observers: mean difference 21.2 days, 95% CI 13.5-28.9; P<.001). The sputum conversion rates in the VOT and DOT groups were 73% and 61.5%, respectively (P=.17). ConclusionsSmartphone-based VOT significantly outperformed community-based DOT in ensuring compliance with tuberculosis treatment among observers. However, the study was underpowered to confirm improved compliance among patients with pulmonary tuberculosis and to detect differences in sputum conversion rates. Trial RegistrationThai Clinical Trials Registry (TCTR) TCTR20210624002; https://tinyurl.com/3bc2ycrh International Registered Report Identifier (IRRID)RR2-10.2196/38796